The effect of acupuncture stimulation on alleviating emotional changes due to acute alcohol administration and the possibility of sigma1 receptor involvement - Su Yeon Seo; Soo Phil Kim; Se Kyun Bang; Suk Yun Kang; Seong Jin Cho; Kwang-Ho Choi; Yeonhee Ryu (Integrative Medicine Research)
Background: Most ETOH addiction preclinical studies have focused on the rewards of chronic ETOH self-administration or the ETOH reinstatement model. Acute ETOH administration studies are scarce despite the potential of ETOH to cause sedation, intoxication and reduced acute functional tolerance. Here, we established a rat model of acute ETOH administration induced by an intraperitoneal injection of 1 g/kg ethanol and assessed the similarities in physiological and behavioral effects between acupuncture and Sigma1 R antagonists. Methods: Male Wistar rats (300−330 g) received pretreatment with (1) saline injection, (2) saline + mechanical stimulation using a mechanical acupuncture instrument (MAI) for acupuncture at the Shenmen (HT7), (3) ETOH (1 g/kg) injection, (4) ETOH + HT7, or (5) the selective σ1 R antagonist BD 1047 (3, 10, or 30 mg/kg, intraperitoneal (IP) injection). ETOH (1 g/kg) or saline was IP injected after 10 min. Then, ETOH-induced immobility was evaluated in an open field arena, ultrasonic vocalizations (USVs) indicating ethanol-induced emotional changes were recorded in a recording chamber, and the rats were sacrificed for the analysis of protein levels of σ1 R in several regions of the brain. Results: Acute ethanol exposure increased the immobile time, 22-kHz USVs, and protein levels of σ1 R in the ventral tegmental area (VTA). However, pretreatment with acupuncture at HT7 induced recovery of immobile time, reduced 22-kHz USVs, and regulated the protein levels of σ1 R in the VTA. These effects have similarities with IP injection of BD 1047 (10 mg/kg). Conclusion: This study showed that acupuncture at HT7 regulates immobility and 22-kHz USVs via Sigma1 R in the VTA upon acute ETOH exposure.